Patients outside hospital. - United States. Army. Signal Corps (photographer):::Creator::::::::::::; Flaherty, John Melvin (collector):::Contributor::::::::::::
Photograph shows convalescing evacuee patients on the lawn behind the center hospital at Puyallup, Washington Assembly Center while nurses and orderlies attend them.